Edible birds nest impact on rats uterine histomorphology, expressions of genes of growth factors and proliferating cell nuclear antigen, and oxidative stress level - Albishtue, Abdulla A. (Veterinary World, 2018)
Aim: This study aimed to evaluate the effect of edible bird’s nest (EBN) supplementation on the uteri of rats based on analyses of the morphological and histomorphometric changes, and expressions of epidermal growth factor (EGF) and its receptor (REGF) genes, vascular endothelial growth factor (VEGF), proliferating cell nuclear antigen (PCNA), and steroid receptors. Materials and Methods: Twenty-four Sprague Dawley rats were equally distributed into the following four groups: G1 (control), G2, G3, and G4 represented the groups treated with EBN at graded concentrations of 0, 30, 60, and 120 mg/kg body weight (BW) per day for 8 weeks, respectively. During the experimental period, the BW of each rat was recorded weekly. At the proestrus stage of estrous cycle, blood samples were collected from the hearts of anesthetized rats that were later sacrificed. The uteri were removed for histological and immunohistochemical analyses. Results: The EBN-treated groups showed an increase in the weights and lengths of uteri as compared to the control. Results showed that relative to G1 and G2, G3 and G4 exhibited proliferation in their uterine luminal and glandular epithelia and uterine glands, and up-regulated expressions of EGF, REGF, VEGF, PCNA, and progesterone receptor, and estrogen receptor in their uteri. The EBN increased the antioxidant (AO) and total AO capacities and reduced the oxidative stress (OS) levels in non-pregnant rats. Conclusion: Findings of this study revealed that EBN promotes proliferation of the uterine structures as evidenced by the upregulation of the expressions of steroid receptors,EGF, REGF, VEGF, and PCNA in the uterus and increased in the plasma concentrations of AO and reduced levels of OS.